PERBAIKAN TEKNOLOGI BUDIDAYA PADI RAMAH LINGKUNGAN POTENSI HASIL TINGGI MELALUI PENGELOLAAN HARA DI LAHAN BUKAAN BARU - Idrus Hasmi; L. M. Zarwazi; Dukat Dukat (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2019)
developed. This study aims to obtain optimum fertilization technology in several new high yielding rice varieties with high yield potential in new open fields. Research has been carried out in new openings in two locations, namely in West Kalimantan Province, with the criteria for new openings in the first location are new openings less than 5 years old and the second location is openings aged 5-10 years after opening. The study refers to a split plot design with 3 replications. The main plot is fertilization level consisting of (R1) Fertilizer dosage recommendations for new openings, (R2) PTT recommended dosage fertilizers, (R3) Fertilizer dosage way of farmers (local), as plots are (V1) Inpara 9, (V2) Inpari 22, (V3) Inpari 30. Research results show that in new openings of land aged <5 years, inpari 22 has a significant effect on the formation of panicles per clump and percent grains of contents while inpari 30 has an effect on increasing the weight of 1000 grains. In newly opened land of 5-10 years, inpari 22 had a significant effect on the formation of panicles per clump while inpari 30 had an effect on increasing percent grains of content and weight of 1000 grains. The dosage treatment with recommended fertilizer dosages for new openings and inpari 22 has a tendency to produce the highest MPD results in new openings with land age <5 years. The dosage treatment with the recommended PTT fertilizer dosage and inpari 30 variety has a tendency to produce the highest MPD results in new openings with a land age of 5-10 years.